2020
DOI: 10.1101/2020.03.16.20035105
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute myelitis after SARS-CoV-2 infection: a case report

Abstract: We report a case of acute myelitis in a patient infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). A 66-year-old man with coronavirus disease 2019 was admitted with acute flaccid paralysis of the bilateral lower limbs and urinary and bowel incontinence. All serum microbiological test results were negative, except for SARS-CoV-2 nucleic acid testing.Clinical findings indicated post-infectious acute myelitis. He received treatment containing ganciclovir, lopinavir/ritonavir, moxifloxacin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
198
1
22

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(231 citation statements)
references
References 19 publications
2
198
1
22
Order By: Relevance
“…4 Another case report from China described acute myelitis as a complication of COVID-19 presenting with flaccid lower limb weakness and persistent fever; a lumbar puncture was not performed but the authors felt the likely cause of myelitis was a post-viral inflammatory process. 5 As illustrated with this unusual case of rhombencephalitis, with evidence for a wider multi-system inflammatory response and the development of neurological symptoms over time, it is important to be vigilant for late non-respiratory manifestations of COVID-19 infections.…”
Section: Discussionmentioning
confidence: 98%
“…4 Another case report from China described acute myelitis as a complication of COVID-19 presenting with flaccid lower limb weakness and persistent fever; a lumbar puncture was not performed but the authors felt the likely cause of myelitis was a post-viral inflammatory process. 5 As illustrated with this unusual case of rhombencephalitis, with evidence for a wider multi-system inflammatory response and the development of neurological symptoms over time, it is important to be vigilant for late non-respiratory manifestations of COVID-19 infections.…”
Section: Discussionmentioning
confidence: 98%
“…Kang Zhao et al reported acute myelitis in a 66-year-old male form Wuhan city who presented with fever and body aches. 22 Mao and colleagues reported six case of CVA in their cohort of 214. 11 There were five ischemic and one case of hemorrhagic stroke.…”
Section: Acute Myelitismentioning
confidence: 99%
“…Although as a cause of AFP has not been reported until now [5]. Yet, there was one study reported a post-infectious acute myelitis as probable COVID-19 complication [6].Here, we reported a very rare complicated case of early-onset ATM following a SARS-CoV-2 respiratory infection.…”
Section: Discussionmentioning
confidence: 70%
“…It was intriguing that ACE2 receptors were also expressed on the membrane of spinal cord neurons. Furtherly, suggesting that SARS-CoV-2 was implicated in acute myelitis by the speci c ACE2 receptors on the surface of spinal cord neurons [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation